Application of Partial Least Square to Assess the Impact of Collaboration Networks on Innovation from MSEs’ Soybean Processing - Nurwullan, Elya - (Informatika Pertanian, 2015)
Structural Equation Model (SEM) alternative method Partial Least Square (PLS) is an analysis tools are usually used to develop a causality model of linear-predictive relation between a collaboration network as the latent exogenous variables (Xi), and the innovation and performance as the latent endogenous variables (Yi ) which has non-parametric with theoretically less supported. This paper aims to discuss the use of PLS on the indirect effects of on the performance of SMEs collaboration networks to soybean processing MSEs’ performance mediated by the level of innovation. This survey is an empirical study conducted in several clusters processing industry center and tofu in 4 regions namely Sumedang District, Tegal regency, West Jakarta and South Jakarta. Selection of research using purposive sampling location is the tofu and tempeh clustered. Based on the analysis, obtained a description that use the PLS on the effect on the performance of SMEs cooperation networks soybean processing mediated by the level of innovation demonstrated relatively good results. Therefore, the application of the model could be widely applied to the various innovation adopting process, especially on the collaboration with external parties in the food and agriculture based industry.